2010
DOI: 10.1111/j.1471-4159.2010.06797.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical changes in the developing rat hippocampus during prolonged hypoglycemia

Abstract: This report reviews laryngoplastic techniques for correction of bowing of the vocal cords, with special consideration to the anatomic details of the anterior commissure. I present a new technique in which the glottic gap is closed by bilateral medialization. This technique may be superior to those described previously, since the correction achieved at the time of surgery is maintained by the placement of Silastic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 60 publications
8
56
0
Order By: Relevance
“…37 Insulin injection to the STZ-treated animals caused significant decreases of the Glu level in the striatum at 4 days, and in the striatum and hippocampus at 4 weeks ( Figure 5). Previous studies have demonstrated reduced Glu level in the brain of nondiabetic rats 14 and T1DM patients 38 after insulin injection. It has been suggested that the mechanism underlying these observations is likely related to the fact that the brain can use Glu as an alternative substrate for energy metabolism in response to insulininduced hypoglycemia.…”
Section: Glutamate Reduction After Insulin Injectionmentioning
confidence: 90%
See 2 more Smart Citations
“…37 Insulin injection to the STZ-treated animals caused significant decreases of the Glu level in the striatum at 4 days, and in the striatum and hippocampus at 4 weeks ( Figure 5). Previous studies have demonstrated reduced Glu level in the brain of nondiabetic rats 14 and T1DM patients 38 after insulin injection. It has been suggested that the mechanism underlying these observations is likely related to the fact that the brain can use Glu as an alternative substrate for energy metabolism in response to insulininduced hypoglycemia.…”
Section: Glutamate Reduction After Insulin Injectionmentioning
confidence: 90%
“…It has been suggested that the mechanism underlying these observations is likely related to the fact that the brain can use Glu as an alternative substrate for energy metabolism in response to insulininduced hypoglycemia. 14,38 It is interesting to note that insulin-induced reductions of Glu level at 4 weeks were observed in the absence of severe hypoglycemia. In the model of STZ-induced T1DM with uncontrolled blood glucose level, the brain appears to be in a hypermetabolic state, and uses greater amounts of energy substrate than normal.…”
Section: Glutamate Reduction After Insulin Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,18 Studies in rats demonstrated that during the transition to an isoelectric electroencephalogram (EEG) in the setting of hypoglycemic coma reductions in Glu, glutamine (Gln) and Lac levels are accompanied by an increase in aspartate (Asp) before a precipitous drop in the phosphocreatine-to-creatine (PCr/Cr) ratio indicative of energy failure. [18][19][20][21] Whether similar changes also occur in the human brain is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This approach encompassed the reliable quantification of a neurochemical profile of several metabolites including Lac, Asp, and Gln, which have been observed to change upon severe hypoglycemia in the rat brain. [18][19][20][21] Hence, the changes in the levels of these additional neurochemicals were investigated in an exploratory fashion.…”
Section: Introductionmentioning
confidence: 99%